Challenges of Anesthetic Management in Pediatric Patients with Hernia Inguinalis Lateralis Dextra Reponibilis: A Case Report - Lestari, Puspita Wahyu; Muh Iswan Wahab; Gede Indrajaya (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Hernia inguinalis lateralis dextra reponibilis (HILD repr.) is a common condition in infants and children, but anesthetic management in these pediatric patients requires special attention. Children's unique physiological and pharmacological characteristics, potential comorbidities, and risk of postoperative pain demand a careful and integrated approach. Case presentation: This case report presents comprehensive anesthetic management of a 6-month-old male infant who underwent elective herniotomy for HILD repr. The anesthesia procedure involved induction with sevoflurane and fentanyl, maintenance of anesthesia with sevoflurane, and multimodal pain management with paracetamol and bupivacaine. The surgery was successful without complications, and the patient recovered well. Conclusion: This case highlights the importance of implementing modern anesthetic practices in pediatric patients with HILD repr., including selection of appropriate anesthetic agents, close monitoring, and multimodal pain management. Specific challenges such as unique airway anatomy, variability in drug pharmacokinetics, and risk of perioperative complications are also highlighted. The successful anesthetic management of this case highlights the importance of an individualized approach and close monitoring to optimize clinical outcomes and minimize complications in pediatric patients with HILD repr.